Determination of Desferrioxamine in the Drug Desferal™ as DFOM-Au (III) Complex by Using Indirect Electrothermal Atomic Absorption Spectrometry and Other Techniques. (Baghdad Science Journal, 2025)
An indirect method using electrothermal atomic absorption spectrometry (ETAAS) has been established for the determination of DFOM in the drug desferal™as DFOM-Au (III) complex. The formation of this complex at 1:1 mole ratio computed by UV-Vis spectrophotometric technique was confirmed by distinction of the IR absorption spectra between the free DFOM and its complex. Several experimental factors that effect the formation of DFOM-Au (III) complex were optimized using AA responses. Aliquots of the complex extract were injected into a coated GF and the AA-signals measured. A direct calibration graph was constructed and from which the figures of merits were found such as: LDR (0.08-3.5 µg ml-1), m0º (293.3 pg), LOD (0.0154 µg ml-1), RSD% (2.0-3.5), recovery present (101.54±0.86), and %Erel (1.54). The established indirect ETAAS was applied to analyze the drug desferal™ for the determination of DFOM using direct and standard additions procedures and DFOM found to be 488 and 484 mg/unit respectively compared to the stated value of 500 mg/unit. All statistical calculations were implemented via the chemsoftware (Minitab version 11).